2021
DOI: 10.3390/jcm10174001
|View full text |Cite
|
Sign up to set email alerts
|

Model of Care for Microelimination of Hepatitis C Virus Infection among People Who Inject Drugs

Abstract: Background: People who inject drugs (PWID) are the largest group at risk for HCV infection. Despite the direct acting antivirals (DAA) advancements, HCV elimination has been hindered by real-life difficulties in PWID. Aims: This study aimed to assess the impact of a multidisciplinary intervention strategy where HCV screening, treatment and follow-up were performed at the same location on efficacy and safety of DAA-therapy in real-life PWID population. Methods: All HCV-infected PWID referred to five specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[83]-[86], geographical area [87]-[89], sexual behavior (e.g., MSM, sex workers) [90], [91], or high-risk of infection (e.g., drug users) [92] with the goal to achieve local elimination, so-called micro-elimination [75],…”
Section: Discussionmentioning
confidence: 99%
“…[83]-[86], geographical area [87]-[89], sexual behavior (e.g., MSM, sex workers) [90], [91], or high-risk of infection (e.g., drug users) [92] with the goal to achieve local elimination, so-called micro-elimination [75],…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to associate harm reduction interventions simultaneously with the administration of safe and short therapeutic regimens may favor a lowered transmission of the virus and a reduction of liver damage in these populations [ 9 , 10 ]. For these reasons, alternative models of care in out-of-hospital setting are spreading in Europe and Italy, with encouraging results [ 24 , 25 , 26 ]. Our study showed how an out-of-hospital care model might guarantee a greater percentage of patients starting DAAs with an overall better retention in care for difficult-to-reach groups with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of peer educators may have contributed to improve the linkage to care in the out-of-hospital setting. Starting treatment quickly and in a more individualized way improved the retention in care of PWID [ 17 , 20 , 24 , 26 ]. In agreement with our findings, recent research conducted in Vienna on DAAs administration as DOT (given at OST facilities) in PWID showed excellent SVR12 rates (99%) in this difficult-to-treat population, similar to patients with expected high treatment compliance in a standard setting [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, 89% of them had their HIV status ever ascertained [87], demonstrating that, in this context, offering testing at home considerably decreased the cost of testing. Testand-treat strategies have also been employed in smaller trials, for specific demographic subgroups, defined by social status (e.g., incarcerated individuals) [88-91], geographical area [92][93][94], sexual behavior (e.g., MSM, sex workers) [95,96], or risk of infection (e.g., drug users) [97] with the goal to achieve local elimination, so-called micro-elimination [98,99]. Some of these trials achieved very high participation and testing rates from the eligible populations, much larger than those reported in the studies of the general population.…”
Section: Plos Onementioning
confidence: 99%